Diffusion‐weighted magnetic resonance imaging is useful for assessing inflammatory myopathies. Issue 5 (14th February 2019) - Faruch, Marie; Garcia, Ana Isabel; Del Amo, Montse; Pomes, Jaume; Isern, Jaime; González, Sergio Prieto; Grau, Josep María; Milisenda, José César; Tomas, Xavier
ABSTRACT: Introduction: Short tau inversion recovery (STIR) sequences in whole‐body MRI are usually used for detecting muscle edema (ME) in inflammatory myopathies. We evaluated b‐value 800 diffusion‐weighted imaging (b800 DWI). Methods: Two radiologists independently and a consensus reader retrospectively reexamined 60 patients with inflammatory myopathies and 15 controls. For each participant, 78 muscles were analyzed with 3 sets of imaging acquisitions: T1‐weighted (T1) turbo spin echo and STIR; T1 and DWI; and T1, STIR and DWI. Mean edema per patient was compared between sequences. Agreement was evaluated. Results: Diffusion‐weighted imaging detected more ME compared with STIR ( P  < 0.001). Agreement between readers was better with both sequences (k = 0.94) than with b800 DWI (k = 0.89) or STIR (k = 0.84) alone. Discussion: Diffusion‐weighted imaging is a valuable add‐on for the study of inflammatory myopathies. Muscle Nerve 59:555–555, 2019